Hypoxic Modulation of HLA-G Expression through the Metabolic Sensor HIF-1 in Human Cancer Cells - Marica Garziera; Lucia Scarabel; Giuseppe Toffoli (Journal of Immunology Research)
The human leukocyte antigen-G (HLA-G) is considered an immune checkpoint molecule involved in tumor immune evasion. Hypoxia and the metabolic sensor hypoxia-inducible factor 1 (HIF-1) are hallmarks of metastasization, angiogenesis, and intense tumor metabolic activity. The purpose of this review was to examine original in vitro studies carried out in human cancer cell lines, which reported data about HLA-G expression and HIF-1 mediated-HLA-G expression in response to hypoxia. The impact of HLA-G genomic variability on the hypoxia responsive elements (HREs) specific for HIF-1 binding was also discussed. Under hypoxia, HLA-G-negative cell lines might transcribe HLA-G without translation of the protein while in contrast, HLA-G-positive cell lines, showed a reduced HLA-G transcriptional activity and protein level. HIF-1 modulation of HLA-G expression induced by hypoxia was demonstrated in different cell lines. HLA-G SNPs rs1632947 and rs41551813 located in distinct HREs demonstrated a prominent role of HIF-1 binding by DNA looping. Our research revealed a fine regulation of HLA-G in hypoxic conditions through HIF-1, depending on the cellular type and HLA-G genomic variability. Specifically, SNPs found in HREs should be considered in future investigations as markers with potential clinical value especially in metastatic malignancies.